2019
DOI: 10.14254/2071-8330.2019/12-4/2
|View full text |Cite
|
Sign up to set email alerts
|

From the Russian food import ban to free trade from Lisbon to Vladivostok – will farmers benefit?

Abstract: With the implementation of the Russian import ban as a countermeasure to the EU sanctions in the context of the Ukrainian crisis, trade relations between the EU and Russia reached their lowest level in 2014. In this paper, we model several trade policy scenarios and assess their effects on domestic agricultural production and trade in Russia, the EU and Germany for the 2020-30 period. The results of the applied general equilibrium MAGNET model suggest that the removal of the Russian food import ban will affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…From this point of view, there is little incentive for the Russian government to lift the import ban. Moreover, as was shown by Banse et al [21], the scenario with no import ban for years 2017-2030 shows that milk production in Russia will decrease by an average of 0.8% annually.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…From this point of view, there is little incentive for the Russian government to lift the import ban. Moreover, as was shown by Banse et al [21], the scenario with no import ban for years 2017-2030 shows that milk production in Russia will decrease by an average of 0.8% annually.…”
Section: Discussionmentioning
confidence: 80%
“…Banse et al [21] assessed several trade policy scenarios and has suggested that possible removal of the Russian import ban will affect Russian agricultural production only to a limited extent, while there will be no effect on the EU. At the same time, depending on how competitive Russian farmers become, creation of free trade area from Lisbon to Vladivostok would benefit farmers in the EU more than farmers in Russia.…”
Section: Introductionmentioning
confidence: 99%
“…• the importance of a sanction episode (Drezner, 1999) • the cost of sanctions for the sender (Dong & Li, 2018;Whang & Kim, 2015) • the stability and power of the leaders in the target country (Spaniel & Smith, 2015) • the power of the military force in the target country (McCormack & Pascoe, 2015) • the economic and political relations between the two countries (Taehee Whang, 2010) • the behavior of third parties (Han, 2018) • the effects of a countermeasure on individuals in both parties (Banse, Duric, Götz, & Laquai, 2019), or on the outcome of the game (Saparaliyev, Mokin, Movkebayeva, Saiymova, & Mustafina, 2019;Veebel & Markus, 2018a) • the cost of sanctions on the target (Bimbetove et al, 2019;Dong & Li, 2018;Gharibnavaz & Waschik, 2018;Salman, Shin, & Shin, 2019) • the internal dynamics of both countries and the role of the opposition party (Onder, 2020) The intensity of sanctions imposed on controversial policies of target states has been also discussed within public choice framework (Kaempfer & Lowenberg, 1988).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They have not discussed whether Russian counteractions is agriculture will change or have changed the sanctions' outcome, be it a lift of the sanctions or a retreat from Ukraine by the Russian troops. (Banse et al, 2019) Veebel and Markus have distinguished countermeasures as a choice for the sanctioned country (which is Russia in their study). However, they have considered this option to be one of many (options or) bids that Russia can make in a dollar-auction game model.…”
Section: The Effects Of the Possibility Of A Fight-back Strategymentioning
confidence: 99%
“…General aspects of the impact of sanctions on the Russian economy are reflected in the works of E. Gurvich et all [3], L. Tyll et all [4], M. Seifullaeva et all [8], I. Korhonen et all [9]. Scenario conditions for the development of agriculture in Russia, the EU and Germany are presented in the work of M. Banse et all [5]. The reverse impact of sanctions on the economy of the European Union was investigated by C. Nasulea et all [6], K. Oja [12].…”
Section: Introductionmentioning
confidence: 99%